Implications of Media Convergence in The Existence of Mass Media in Banten - Indrianti Azhar Firdausi; Ichsan Adil Prayogi; Saskia Pebriane (Unisba Press, 2022)
This article discusses how media convergence has implications for the existence of local mass media in Banten, seen by media convergence technology and at the same time transforming to change as digital media by reconstructing editorial policies, media organizations, and media management. This article uses a case study research method on several online media in Banten. This study concludes that the policy of media convergence amid competition and the growth of the mass media business is the right step in developing and maintaining the existence of mass media in Banten. By implementing a convergence strategy in various fields, including the transformation of editorial policy which has implications for the mixing of editorial and non-editorial duties with the aim of equitable distribution of income. Meanwhile, changes in the form of information content presented no longer prioritize local issues, but rely on more general and viral issues.